IL-4-activated C/EBPβ is involved in alveolar macrophage polarization towards the M2 phenotype during pulmonary fibrosis induced by single-walled carbon nanotubes. Issue 11 (30th September 2022) - Zhang, Xiang; Zhu, Jiaojiao; Yang, Shuxin; Yao, Zhuomeng; Zhao, Sujuan; Wang, Yan; Zhou, Chengfan; Zhu, Qixing; Shen, Tong
Abstract : IL-4-activated C/EBPβ participated in SWCNT-mediated M2 AM polarization and fibrogenesis, and IL-4 may serve a therapeutic target for nanoparticle-induced fibrogenesis. Abstract : Given the rapid development in the field of nanotechnology, the potential toxicity of carbon nanotubes (CNTs) in humans has received much attention in recent years. However, the exact mechanisms are still not clear. The current study aimed to investigate the role of alveolar macrophage (AM) polarization during pulmonary fibrosis induced by CNTs, as well as the underlying molecular mechanism of SWCNT-induced pulmonary fibrosis. In vivo, C57BL/6J mice were intratracheally instilled with single-walled CNTs (SWCNTs), short-type multi-walled CNTs (s-MWCNTs) and long-type multi-walled CNTs (l-MWCNTs). Then, AM polarization and pulmonary inflammation and fibrosis were evaluated on days 3, 7 and 28. The results showed that CNTs promoted AM polarization towards the M1 phenotype and pulmonary inflammation during the early stage, while AMs were polarized towards the M2 phenotype, which was accompanied by pulmonary fibrosis during the late stage. Notably, SWCNTs have the strongest capacity to induce M2-type AM polarization and pulmonary fibrosis among the three types of CNTs. Mechanistically, the interleukin-4 (IL-4) levels in bronchoalveolar lavage fluid were upregulated in SWCNT-exposed mice, and C/EBPβ was the most markedly upregulated gene among 15 polarization-related genes in AMs from SWCNT-exposed mice. Abolishing IL-4 with an IL-4 neutralizing antibody (IL-4 NA) inhibited C/EBPβ upregulation and AM polarization towards the M2 phenotype and ameliorated SWCNT-induced pulmonary fibrosis. In vitro, knockdown of C/EBPβ using C/EBPβ siRNA reduced SWCNT-induced M2 AM polarization and ameliorated epithelial–mesenchymal transition and myofibroblast activation that were two critical stages during the development of fibrosis. In summary, we identified that IL-4-activated C/EBPβ participated in SWCNT-mediated M2 AM polarization and subsequent pulmonary fibrosis. Our findings provide new evidence for understanding the mechanism of CNT-induced pulmonary fibrosis, and IL-4 may be useful as a diagnostic biomarker and therapeutic target for nanoparticle-induced fibrogenesis.